Family Support With Self-Care Management For Hypertension Patients - Bayu Dwisetyo; Intan Safina (International Journal of Public Health, 2024)
Hypertension is a disorder characterized by elevated blood pressure originating from abnormalities in blood vessels, leading to impaired delivery of oxygen and nutrients to essential body tissues. Family involvement in assisting relatives afflicted with hypertension constitutes a supportive mechanism to facilitate effective self-care management of the condition.This study aimed to investigate the correlation between familial support and self-care management in hypertensive patients at Tuminting Health Center. Cross-sectional methods. The study sample comprised 49 individuals selected by purposive sampling. A questionnaire was employed as the study instrument. The gathered data was analyzed with the SPSS 16.0 software employing the Chi Square statistical test at a significance level (α) of <0.05. The results indicated that the predominant age group was 56-65 years, including 27 respondents, which represents 55.1%. The majority of respondents were female, totaling 39 individuals, accounting for 79.6%. The most common educational attainment was high school, with 22 respondents, corresponding to 44.9%. The statistical test yielded a P value of 0.0001, which is less than the alpha value (α) of ≤0.05. This study concludes that a correlation exists between family support and self-care management in hypertension patients at Tuminting Health Center. The findings of this study are anticipated to serve as a resource for individuals with hypertension, emphasizing the importance of self-care management to prevent problems and facilitate recovery.